Role of C3a Receptors, C5a Receptors, and Complement Protein C6 Deficiency in Collagen Antibody-Induced Arthritis in Mice - Banda, Nirmal K. (2011)
The complement system, especially the alternative pathway (AP), plays essential roles in the induction of injury in collagen antibody-induced arthritis (CAIA) in mice. The goal of the current study was to directly compare the roles of receptors for C3a and C5a, as well as the membrane attack complex (MAC), as effector mechanisms in the pathogenesis of CAIA. Clinical disease activity (CDA) in C3aR(−/−), C5aR(−/−), and C6 deficient (C6-def) mice was decreased by 52%, 94%, and 65%, respectively, as compared with WT mice. Decreases in histopathologic injury as well as in IgG and C3 deposition paralleled the CDA. A decrease in the percentage of synovial neutrophils was observed in C3aR(−/−), C5aR(−/−), and C6-def mice, and a decrease in macrophages was observed in C3aR(−/−) and C5aR(−/−), but not in C6-def, mice. Synovial mRNA obtained by laser capture microdissection exhibited a decrease in TNF-α in C5aR(−/−) mice and in IL-1β in both C5aR(−/−) and C6-def mice, while C3aR(−/−) mice demonstrated no change in either cytokine. Our findings show that absent C3aR-, C5aR- or MAC-initiated effector mechanisms each decreases susceptibility to CAIA, with clinical effects most pronounced in C5aR deficient mice. Although the absence of C3aR, C5aR, or C6 led to differential deficiencies in effector mechanisms, decreased proximal joint IgG and C3 deposition was common to all three genotypes in comparison to WT mice. These data suggest the existence of positive feedback amplification pathways downstream of all three effectors that promote additional IgG deposition and C3 activation in the joint.